THE CHRISTIAN'S DILEMMA: ORGANICISM OR MECHANISM?: with Fraser Watts and Michael J. Reiss, "Holistic Biology: What It Is and Why It Matters"; Michael Ruse, "The Christian's Dilemma: Organicism or Mechanism?"; David J. Depew and Bruce H. Weber, "Developmental Biology, Natural Selection, and the Conceptual Boundaries of the Modern Evolutionary Synthesis"; Ilya Gadjev, "Epigenetics, Representation, and Society"; Harris Wiseman, "Systems Biology and Predictive Neuroscience: A Double Helical Approach"; Richard Gunton and Francis Gilbert, "Laws in Ecology: Diverse Modes of Explanation for a Holistic Science"; and Niels Henrik Gregersen, "The Exploration of Ecospace: Extending or Supplementing the Neo‐Darwinian Paradigm?". Issue 2 (June 2017) - Ruse, Michael
Abstract: Is organicism inherently Christian‐friendly, and for that matter, is mechanism inherently religion nonfriendly? They have tended to be, but the story is much more complicated. The long history of the intertwined metaphors of nature taken as an organism, versus that of nature as a machine, reveals that both metaphors have flourished in the endeavors of philosophers, scientists, and persons of faith alike. Different kinds of Christians have been receptive to both organicist and mechanistic models, just as various kinds of nonreligious scientists have been receptive to both holistic and machine metaphors. Although, it is true, organicism has been generally more attractive to persons of faith than mechanism (and vice versa), an overview of the rich and varied history of allegiances to these metaphors—religious and nonreligious alike—shows that debate is much more interesting and complex. A brief inspection of conversation surrounding recent scientific discoveries shows that this debate between metaphors is still very much alive today.